Die Stadt Bam und ihr Oasen-Umland/Zentraliran.: Ein Beitrag zu Theorie und Praxis der Beziehungen ländlicher Räume zu ihren kleinstädtischen Zentren im Orient - Ehlers, Eckart (ERDKUNDE, 1975)
The paper examines the linkages between a small oriental town and its agrarian umland. The basis of investigation is an analysis of the economic and agrarian social structure in the oasis settlements of Bam (Sec. 2, Figs. 1-3) and examination of the functional provision of the town of Bam as the urban centre of the study area (Sec. 3, Fig. 4). In terms of Bobek's theory of rent-capitalism, there are a number of basic types of town-umland relationships, all of which operate to the advantage of the town of Bam and to the disadvantage of the rural areas. In addition to the function of the town as the seat of the landowners, the bazaar trade is especially prominent in the parasitical exploitation of the country side- either through the 'pish-foroush' system in which country people pawn part of their expected har vest on poor terms at the bazaar in return for money or goods; or because the lack of rural infrastructure means that all daily, periodic or episodic shopping requirements can only be met in the town. The modern development of a town-concentrated tertiary sector strengthens this tendency. Fig. 5 shows in schematic form the rent-capitalistic and central-place linkages between the countryside and the town.